Transition to bereavement: A prospective longitudinal study of health-related quality of life in informal caregivers of oldest-old individuals - Alves, Sara; Paúl, Constança; Ribeiro, Oscar (Frontiers in Medicine, 2022)
Introduction: Experiencing bereavement may be challenging. Despite the oldest-old population increase, a subgroup at greater risk of death, few studies focus on the grieving process of ICs. This study analyzed the transition to bereavement of ICs of oldest-old individuals (≥80 years) over one-year and compares the evolution of the health-related quality of life (HrQoL) between those experiencing bereavement and those who continued care through the study period. Material and Methods: A prospective longitudinal observational study was conducted enrolling 204 ICs of the Metropolitan Area of Porto (North Portugal), of which 36 experienced the death of care receiver (CR). ICs’ health profile and burden were assessed. CRs’ functional and cognitive status were also appraised. Results: Bereaving caregivers were mostly female, CRs’ children, and had on average 60.4 years at baseline. Caregivers spent a mean of 10.1 hours/day (SD=7.7) caring, for 80.6 months (SD=57.5). The time elapsed since CR’s death was 6 months (SD=3.5) from entering in the study. CRs who died had a mean age of 88.3 (SD=5.4) years at baseline, and were very dependent. Over a one-year follow-up, bereaving caregivers showed a significant decrease in mental health following CR’s death; on the other hand, caregivers who continued caring improved mental health [F(1,159)=4.249, p=0.041]. Discussion: Ending the caregiver career was marked by a decline in mental health whereas to continue caring was marked by an improvement in this outcome. While it is highly expected that the CR's death will be perceived as a relief considering both the caregiver's characteristics (e.g., medicines) and the CR condition (e.g., high dependence levels), the results suggest an opposite direction. CRs’ death seems to arise an emotional burden for IC, at least during the first year, possibly triggering feelings of loneliness and a life without purpose that seems to aggravate mental health issues. Conclusion: The transition to bereavement among ICs seems to lead to a caregiver mental health decline while those who continued caring (and thereby, experiencing caregiving stressors) seems to improve in this outcome. Ceasing caregiving stressors does not seem to contribute better experiencing bereavement among ICs, suggesting the need for support throughout this phase.